2019
DOI: 10.1128/msystems.00431-19
|View full text |Cite
|
Sign up to set email alerts
|

Ifenprodil and Flavopiridol Identified by Genomewide RNA Interference Screening as Effective Drugs To Ameliorate Murine Acute Lung Injury after Influenza A H5N1 Virus Infection

Abstract: Drug repurposing is a quick and economical strategy for developing new therapies with approved drugs. H5N1 is a highly pathogenic avian influenza virus subtype that can cause severe acute lung injury (ALI) and a high mortality rate due to limited treatments. The use of RNA interference (RNAi) is a reliable approach to identify essential genes in diseases. In most genomewide RNAi screenings, virus replication is the readout of interference. Since H5N1 virus infection could induce significant cell death and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…These screens identified multiple genes for which knockdown altered cell viability and drugs targeting some of these genes were assayed for their potential antiviral activity. The neurological drug ifenprodil increased cell viability in vitro and markedly decreased leukocyte infiltration and lung injury, and improved survival of mice infected with H5N1 ( Zhang et al, 2019 ), the most lethal influenza virus strain. The effect of ifenprodil was discussed in the context of its antagonism at the N-methyl-D-aspartate (NMDA) receptor as overstimulation of the NMDA receptor can trigger lung injury.…”
Section: Sigma-1 Receptor Ligands Exert Antiviral Activitymentioning
confidence: 99%
“…These screens identified multiple genes for which knockdown altered cell viability and drugs targeting some of these genes were assayed for their potential antiviral activity. The neurological drug ifenprodil increased cell viability in vitro and markedly decreased leukocyte infiltration and lung injury, and improved survival of mice infected with H5N1 ( Zhang et al, 2019 ), the most lethal influenza virus strain. The effect of ifenprodil was discussed in the context of its antagonism at the N-methyl-D-aspartate (NMDA) receptor as overstimulation of the NMDA receptor can trigger lung injury.…”
Section: Sigma-1 Receptor Ligands Exert Antiviral Activitymentioning
confidence: 99%
“…Li et al (Runfeng et al, 2020) pointed out that the traditional Chinese medicine Lianhuaqingwen could significantly inhibit the replication of SARS-CoV-2 in cells, and after the treatment of Lianhuaqingwen, the expression of cytokines induced by virus particles was significantly reduced (Table S1). Based on Zhang et al's research (Zhang et al, 2019), Ifenprodil is considered as a potential first-line drug for the treatment of COVID-19 (Table S1). Duan et al (2020) showed that plasma therapy may provide a useful therapeutic effect and a low risk in the treatment of severe COVID -19 patients (Table S1).…”
Section: The Treatment and Prevention Of Covid-19mentioning
confidence: 99%
“…NP-120 is N-methyl-d-aspartate (NDMA) receptor glutamate receptor antagonist, which targets the NMDA-type subunit 2B (Glu2NB). [97] Ifenprodil is a vasodilator, originally developed by Sanofi as an oral medication to treat blood circulation disorders in French and Japanese markets. It is no longer sold in France but is still marketed in Japan.…”
Section: Chloroquinementioning
confidence: 99%
“…An independent animal study showing a considerable reduction in ALI and enhanced survivability in Avian H5N1 infected mice encourages researchers to expand clinical programs to ALI and ARDS associated with COVID-19 infection. [97] An adaptive Phase IIb/III study assessing the safety and efficacy of ifenprodil (20/40 mg three times a day) together with standard of care in comparison to standard of care alone in the treatment of hospitalized COVID-19 patients is underway (NCT04382924). Ifenprodil is already being tested in clinical trials in patients suffering from IPF and its associated cough (NCT04318704).…”
Section: Chloroquinementioning
confidence: 99%